Family Support and Coping Strategies to The Quality of Life Among Diabetes Mellitus Patients in Rural Area, Indonesia - Dwi Sarwani Sri Rejeki; Hepy Tri Riskia Septianti; Siwi Pramatama Mars Wijayanti (Journal of Applied Science for Pharmaceuticals and Health, 2024)
Research on the quality of life among type II DM patients in rural areas is rarely conducted. This research aimed to analyze the relationship between family support and coping strategies with quality of life among type II DM patients in the rural area. This research is analytic with cross-sectional analytical. Population in this research is all type II of DM patients in Kedungbanteng Community Health Centers, Banyumas Regency which participated in Prolanis DM in 2018 (total of 130 people). The sampling method is based on total sampling with a total of 96 people who meet inclusion and exclusion criteria. Variables in this study were family support, coping strategies, and quality of life which were collected by Questionnaire. The data was analyzed as univariate and bivariate with the Chi-square test The average age of the respondents is 57,59 years. The majority of respondents were female, has basic education level, has DM complications, family support, coping strategies, and quality of life among in high category. There is relationship between family support(p-value:0,006) and coping strategies (p- value:0,000) with quality of life among type II DM patients. There is a correlation between family support and coping strategies with quality of life among type II DM patients. The community needs to increase awareness that family support can improve the quality of life among type II DM patients.